Radiographic Anatomy of the Pediatric Lisfranc Joint. Issue 10 (November 2018) - Knijnenberg, Lisa M.; Dingemans, Siem A.; Terra, Maaike P.; Struijs, Peter A.A.; Schep, Niels W.L.; Schepers, Tim
Abstract : Background: Injuries to the Lisfranc joint in children and adolescents are rare. The incomplete ossification of the bones of the foot makes it difficult to detect injuries. The aim of this study was to determine age-specific radiographic measurements of the Lisfranc joint to provide guidance to the radiologist, emergency physicians, and surgeons to decrease misdiagnosis of Lisfranc injuries and improve detection. Methods: We retrospectively reviewed all foot radiographs without traumatic injury made between August 2014 and February 2015 in all patients younger than 18. The attendance list of the Emergency Department and Outpatient Clinic of a level-1 trauma center were used. Using a non–weight-bearing anteroposterior-view of the foot the distance between the base of metatarsal 1 and metatarsal 2 (MT1-MT2) and the distance between the medial cuneiform (MC) and the base of metatarsal 2 (MC-MT2) were measured. Median normal values were calculated per age. Results: A total of 352 patients between the age of 0 and 18 years were screened for eligibility. Excluded were 109 patients because of anatomic abnormality, a fracture, inadequate radiograph, pain at the base of the first metatarsal, second metatarsal or MC, persisting pain at the Outpatient Clinic checkup or no follow-up. Included in the analysis were 243 patients. Conclusions: The distance between the base of MT1-MT2 was constant below 3 mm. Measurements for both MT1-MT2 and MC-MT2 distance approached adult values at the age of 6. Level of Evidence: Level III.